In vitro evaluation and wound healing cream formulation of Acalypha indica Linn ethanolic extract - Ammar Mahmoud Ibrahim, 1987- author 639459; Razauden Mohamed Zulkifli, supervisor 601463; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2016